Association Between Vitamin D Status and Undernutrition Indices in Children: A Systematic Review and Meta-Analysis of Observational Studies - Chunhua Song; Hongzhi Sun; Ben Wang; Chunli Song; Hongying Lu (Frontiers Media S.A., 2021)
Introduction: Undernutrition, defined as stunting, wasting, and underweight, still implicates millions of infants and children worldwide. Micronutrients have pivotal effects on growth rate. The outcomes of vitamin D deficiency on undernutrition indices have stayed controversial. The object of current study is to answer this question: is there any association between vitamin D status and undernutrition indices?Methods: The international databases were used for a systematic search to identify relevant observational studies in English up to January 2021. A random-effect model was applied to combine the results of included essays.Results: Among 3,400 citations, 7 observational studies (4 cohorts and 3 cross-sectional) were eligible to enter in meta-analysis. Analysis of the lowest 8,295 children indicated that low vs. high serum level of vitamin D is directly associated with a higher risk of wasting (Summary Risk Estimate: 1.30; 95% CI: 1.04, 1.62; I2 = 0%). However, there is no significant association between vitamin status and risk of stunting (Summary Risk Estimate: 1.10; 95% CI: 0.72, 1.70; I2 = 81.6%) and underweight (Summary Risk Estimate: 1.12; 95% CI: 0.81, 1.56; I2 = 49.2%).Conclusion: When comparing low and high serum vitamin D concentration categories, there is an inverse link between vitamin D status and wasting, but no relationship with stunting as well as underweight. However, further prospective and trial studies are required to deepen our understanding of these associations.